PENGELOLAAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI MASA PANDEMI COVID-19 (STUDI PADA MTs SWASTA AL-IHSAN BALEENDAH) - Silviyanti Regina; Khaerul Umam; Fitri Pebriani Wahyu (Universitas Bina Taruna Gorontalo, 2022)
This study aims to find out how the financial management of BOS funds during the Covid-19 pandemic at Al-Ihsan Baleendah Private MTs. Financial management should receive more attention because if financial management is carried out properly, it will facilitate activities and achieve organizational goals. The theory used in the researcher is Mulyasa's financial management theory which includes (1) Financial Planning, (2) Implementation, and (3) Evaluation. The research method used is descriptive qualitative method. Data collection techniques were carried out by interview, observation and documentation. The data analysis technique used is according to Miles & Huberman which consists of data reduction, data display and drawing conclusions. The results of this study indicate that the management of BOS funds at Al-Ihsan Baleendah Private MTs has been running well and smoothly where in financial planning, the preparation of RKAM at Al-Ihsan Baleendah Private MTs has been in accordance with existing technical instructions. Then in Implementation, the distribution is carried out in two stages or per semester. The use of BOS funds in 2020 has complied with the technical instructions. And at the Evaluation stage, supervision of the management of BOS funds at the Al-Ihsan Baleendah Private MTs in 2020 is carried out by the Madrasah Committee. Meanwhile, the LPJ is evaluated by the Regency Ministry of Religion.